Dialektika Filsafat Islam dan Pendidikan dalam Mewujudkan Sistem Pendidikan Berbasis Nilai Ketauhidan - Adi Haryono; Abu Hasan Al Asy'ari; Zainal Abidin; Abd. Haris (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study explores the dialectical relationship between Islamic philosophy and education in constructing a value-based educational system grounded in the principle of tawḥīd (Divine Unity). The research adopts a qualitative, philosophical-hermeneutic approach that is reflective, analytical, and interpretative in nature. It critically examines the ontological, epistemological, and axiological dimensions of Islamic education as conceptualized within the framework of Islamic philosophy. The findings demonstrate that education in Islam is not merely a cognitive transmission of knowledge, but a holistic transformation of the self rooted in metaphysical awareness and spiritual development. Islamic philosophy provides the epistemic foundation that integrates revelation, reason, and human experience into a unified educational paradigm. In contrast to secular Western models that emphasize instrumental rationality and material outcomes, the Islamic educational vision aims to cultivate the insān kāmil—a complete human being—by harmonizing intellectual, moral, and spiritual faculties. The study argues that the Islamization of education is imperative to resist epistemological alienation and restore education's transcendental purpose. Through a critical synthesis of classical and contemporary Islamic thought, this research reaffirms the urgency of grounding educational systems in Islamic metaphysics and ethical values to nurture learners who are not only knowledgeable but also spiritually conscious and socially responsible.